Core Dimensions and Challenges of Türkiye’s Entrepreneurial Ecosystem: Insights for Developing Countries - ATSAN, Nuray; ÖZEN-AYTEMUR, Janset; DİRLİK, Onur (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Within the scope of this study, Türkiye's entrepreneurship ecosystem, which is a representative example for understanding the entrepreneurship ecosystem in developing countries, was examined in terms of human resources and capacity, incentives, funds and financing, support mechanisms and law and regulatory framework dimensions. These dimensions, which are widely accepted as integral components of the entrepreneurship ecosystem in the literature, were examined by taking historical patterns into account. In order to examine the dimensions that constitute the ecosystem, not only the studies in the literature but also the reports published by all relevant institutions were used as data. As a result, the key role of the state as the main actor in the ecosystem was determined, and the critical importance of elements such as technology and institutional mechanisms, including legal grounds, was discussed.